A Time Saving Method to Fabricate a Custom Ocular Prosthesis - Chiramana, Sandeep; Anne, Gopinadh; Ravuri, Kavya; Boppana, Phani Praneetha; Kumar, Sampath; Appana, Krishna Chaitanya (Journal of Orofacial Research, 2013)
Ocular prostheses have a long history of successful use. Several variations of the techniques and materials used have been proposed before. The replication of the natural iris by oil painting requires skill and also takes a lot of time. In this article some alternate procedures have been presented to save time while fabrication of a custom ocular prosthesis. Digital photography was used to replicate the iris of the patient, replacing the conventional oil paint technique. Advantages, such as reduced treatment time and increased simplicity make this method an alternative for fabricating ocular prostheses.